Baseline associations between thoracic expansion, respiratory function, and pain in nonspecific low back pain: A cross-sectional analysis from the DIAFRAGMA trial - Francisco José Vera-Serrano; Maria Jesus Vinolo-Gil; María Rebollo-Ramos; María-José Estebanez-Pérez; José-Manuel Pastora-Bernal; Juan Antonio Díaz-Mancha (PLoS ONE, 2026)
Objective To examine the associations of respiratory variables (chest and abdominal expansion, spirometry) with pain, lumbar mobility, and quality of life in nonspecific low back pain (NSLBP) using baseline data from the DIAFRAGMA trial. Design Cross-sectional study using baseline data from a randomized controlled trial. Participants Fifty subjects (22 females [44%], 28 males [56%]; mean age 45.96 years; BMI 26.97 kg/m²) with NSLBP recruited between January and July 2024. Main measures: Axillary, sternal, and abdominal inspiratory expansion; spirometric parameters (FVC, FEV1); pain via pressure pain thresholds (PPT), Schober test, FFT; and quality of life via SF-12. Methods Pearson correlations assessed relationships between respiratory and clinical variables. Multiple linear regression adjusted for age, sex, and BMI. Significance was set at p < 0.05 with Bonferroni correction. Results Abdominal expansion correlated with FVC (r = 0.45; p < 0.001), FEV1 (r = 0.39; p = 0.003), PEF (r = 0.28; p = 0.03), axillary (r = 0.47; p < 0.001) and sternal expansion (r = 0.58; p < 0.001), PPT at L4 (r = 0.26; p = 0.04) and L5 (r = 0.29; p = 0.02), and SF-12 (r = 0.25; p = 0.04). BMI correlated negatively (r = –0.31; p = 0.02). In regression, abdominal expansion independently predicted pain after adjustment. Conclusions Reduced thoracoabdominal expansion and spirometric performance are associated with greater pain and poorer quality of life in NSLBP, supporting the diaphragm’s role in low back pain.